2022
DOI: 10.1158/2159-8290.cd-22-0686
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Mechanisms of Mismatch-Repair Deficiency Delineate Two Modes of Response to Anti–PD-1 Immunotherapy in Endometrial Carcinoma

Abstract: Mismatch repair-deficient (MMRd) cancers have varied responses to immune checkpoint blockade (ICB). We conducted a phase 2 clinical trial of the PD-1 inhibitor pembrolizumab in 24 patients with MMRd endometrial cancer (NCT02899793). Patients with mutational MMRd tumors (6 patients) had higher response rates and longer survival than those with epigenetic MMRd tumors (18 patients). Mutation burden was higher in tumors with mutational MMRd compared to epigenetic MMRd; however, within each category of MMRd, mutati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 107 publications
0
26
0
Order By: Relevance
“… 56 , 58 We also discovered a splice mutation in JAK1 as a LOF variant (Arg110 splice variant); however, this tumor mutation was recorded in a patient with a partial response to anti-CTLA-4. 56 This highlights that the presence or absence of LOF variants in the IFN-γ pathway in a tumor biopsy is not an absolute determinant of ICB response 64 ; rather, the outcome depends on multiple factors, including the penetrance of the mutation itself (i.e., zygosity), tumor clonal architecture, co-occurring mutations, tumor mutational burden, oncogenic signaling, tumor microenvironment, antigen presentation, and immune checkpoint engagement. 4 , 65 Many of the variants we discovered with functional effects on IFN-γ signaling had clinical precedence, implying that immunoediting in cancer, particularly for immune-hot tumors, may be more prevalent than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“… 56 , 58 We also discovered a splice mutation in JAK1 as a LOF variant (Arg110 splice variant); however, this tumor mutation was recorded in a patient with a partial response to anti-CTLA-4. 56 This highlights that the presence or absence of LOF variants in the IFN-γ pathway in a tumor biopsy is not an absolute determinant of ICB response 64 ; rather, the outcome depends on multiple factors, including the penetrance of the mutation itself (i.e., zygosity), tumor clonal architecture, co-occurring mutations, tumor mutational burden, oncogenic signaling, tumor microenvironment, antigen presentation, and immune checkpoint engagement. 4 , 65 Many of the variants we discovered with functional effects on IFN-γ signaling had clinical precedence, implying that immunoediting in cancer, particularly for immune-hot tumors, may be more prevalent than previously thought.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicopathologic and molecular heterogeneity within molecular subtypes has been noted (Figure 2). Our team and others have shown that the clinicopathologic features of MMR‐deficient/MSI‐H ECs differ according to the mechanism underpinning MSI instability 39–41 . MLH1 ‐hypermethylated ECs were shown to be older, more obese, and had more advanced disease at diagnosis compared to those with germline or somatic MMR gene mutations 39 .…”
Section: Heterogeneity Within the Ec Molecular Subtypesmentioning
confidence: 92%
“…37 ECs differ according to the mechanism underpinning MSI instability. [39][40][41] MLH1-hypermethylated ECs were shown to be older, more obese, and had more advanced disease at diagnosis compared to those with germline or somatic MMR gene mutations. 39 Furthermore, there is evidence to suggest that at least a subset of MLH1 hypermethylated EC patients have worse oncologic outcomes and response to ICB when compared to their gene-mutated counterparts (germline/somatic).…”
Section: Therapeutic Implications Of the Ec Molecular Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Effector CD8þ T cells correlated with regression of mutational MMR-D tumors and activated CD16þ natural killer cells were associated with response to ICI in ECs with MLH1 promoter hypermethylation. 78 This suggests heterogeneity by mechanism of MMR-D that could influence response to immune-based therapies (Table 2). However, the study was limited in sample size and did not include germline assessments.…”
Section: Heterogeneity By Mmr Mechanism In Ecmentioning
confidence: 99%